Nocturnal heart rate during sleep is associated with increased risk of type 2 diabetes mellitus in adults with obstructive sleep apnoea syndrome - Liping Wang; Jiajia Ran; Jingfeng Zou; Shaotian Li; Chunhui Tian; Xin Yang; Yiting Liu; Jingjing Wan; Wen Peng (Annals of Medicine, 2025)
Objective Few studies have confirmed the relationship between nocturnal heart rate (HR) and the risk of type 2 diabetes mellitus (T2DM) in patients with obstructive sleep apnoea syndrome (OSAS), and the aim of this study was to investigate this relationship.Methods The study retrospectively collected and cross-sectionally analyzed the clinical data of 1104 OSAS patients who met the study inclusion and exclusion criteria in the electronic medical record system of Wuhan Union Hospital. All patients underwent polysomnography and an apnea-hypoventilation index ≥5 was considered OSAS. Logistic regression and restricted cubic spline (RCS) regression were used to analyze the association between nocturnal HR and risk of T2DM. The predictive ability of HR for T2DM was analyzed using receiver operating characteristic (ROC) curves. The study was also analyzed in subgroups by age. HR was also classified into three groups, and the associations between different HR levels and T2DM risk were assessed using three logistic regression models.Results The mean age of the subjects was 54.49 (±9.95) years, and 374 subjects had T2DM. Nocturnal HR levels were higher in the T2DM group compared to the non-T2DM group. Multifactorial logistic regression analysis showed that nocturnal HR was significantly associated with the risk of T2DM (OR = 1.02, p = 0.038). ROC analysis showed that the area under the curve for HR was 0.554 (95%: 0.518–0.590). The results of the RCS analysis with additional covariate adjustment indicated a linear positive correlation (p-non-linear > 0.05) between HR and the risk of T2DM. In the subgroup of individuals aged 45–65 years, a progressive increase in the risk of developing T2DM with increasing HR was observed in logistic model 3, which included the most covariates (Q2VSQ1, OR = 1.568, p = 0.047; Q3VSQ1, OR = 1.803, p = 0.018).Conclusion Nocturnal HR was positively correlated with the risk of T2DM in the population with OSAS.